Judicialização e ativismo judicial na mídia - os efeitos da COVID-19 na imagem pública do Judiciário brasileiro - Ribeiro, Desirée Ferreira Marques (2024)
The research focuses on the public image of the Brazilian Judiciary and aims to analyze its potential influence by historical-contextual factors, as depicted in journalistic portrayals of its performance. The primary objective is to comprehend how the media portrayed the Brazilian Judiciary using the terms "judicialization" and "judicial activism," and to assess whether and how this portrayal was impacted by the COVID-19 pandemic. The study encompasses three specific objectives: 1) to comprehend the concepts associated with the terms "judicialization" and "judicial activism" in the twelve months preceding and following the onset of the pandemic; 2) identify the value attributed to these expressions and assess their influence on the public image of the Judiciary; and 3) analyze the thematic framework of news coverage both before and during the COVID-19 pandemic. This research adopts a documentary approach, employing systematic content analysis and thematic framing techniques on news articles published in the Folha de S. Paulo and Globo newspapers from March 20, 2019, to March 20, 2021. The theoretical foundation guiding the analysis revolves around the concept of legitimacy in terms of public support, emphasizing adherence to the values underlying the institution's existence and the decisions it makes. The key finding suggests that the pandemic positively impacted the public image of the Brazilian Judiciary, alleviating persistent criticisms directed at the institution.